Review of the book: Marinelli, P.J. & Laughlin, L.M. (2007). Puentes: Spanish for Intensive and High-Beginner Courses. (Boston: Heinle). - Alice Driver (Universidad de La Sabana, 2009)
Puentes: Spanish for Intensive and High-Beginner Courses is designed to help students with a foundational understanding of Spanish build a bridge or "puente" of knowledge that will provide a smooth transition to the next level of Spanish. The fourth edition has been revised to streamline grammar explanations and place more emphasis on practicing Spanish in conversation. Auxiliary materials accompanying the book include two CD's of listening activities, a video program on DVD, an online activity workbook and an instructor's resource manual.